Συνɛίδησις in Paul's Texts and Stoic Self-Perception - Wilson, Annalisa Phillips (New Testament studies, 2023)
Συνɛίδησις is a relatively rare word, but a favourite for Paul, whose undisputed texts contain nearly half of its New Testament occurrences. In the 19th and 20th centuries, scholars debated the origin of the substantive and the possibility of Stoic influence, which led to a consensus that the term was not a technical philosophical one and Paul's use was not affected by Stoic thought. There is evidence, though, that the presence of συνɛίδησις in a few Stoic texts is due to its semantic relationship in Stoic discourse with συναίσθησις, the Stoic term for self-perception, which was a key component in their epistemological and ethical theory. This article argues that a reading of Paul's use of συνɛίδησις as Stoic self-perception explains the distinctive features of his use to which scholars have recently drawn attention, namely, the permanent and continuous operation of the συνɛίδησις, its ability to be passively impacted by the actions of others and the neutral or positive content of its reflexive knowledge. After a review of recent scholarship, I discuss the role of συναίσθησις in Stoic theory and the evidence for its semantic relationship to συνɛίδησις, then offer a reading of 1 Cor 8-10 demonstrating Paul's use of συνɛίδησις as self-perception.